Structural Characterization of the Highly Restricted Down Syndrome Critical Region on 21q22.13: New KCNJ6 and DSCR4 Transcript Isoforms - Antonaros, Francesca; Pitocco, Margherita; Abete, Domenico; Vione, Beatrice; Piovesan, Allison; Vitale, Lorenza; Strippoli, Pierluigi; Caracausi, Maria; Pelleri, Maria Chiara (Frontiers in Genetics, 2021)
Down syndrome (DS) is caused by trisomy of chromosome 21 and it is the most common genetic cause of intellectual disability (ID) in humans. Subjects with DS show a typical phenotype marked by facial dysmorphisms and ID. Partial trisomy 21 (PT21) is a rare genotype characterized by the duplication of a delimited chromosome 21 (Hsa21) portion and it may or may not be associated with DS diagnosis. The highly restricted Down syndrome critical region (HR-DSCR) is a region of Hsa21 present in three copies in all individuals with PT21 and a diagnosis of DS. This region, located on distal 21q22.13, is 34 kbp long and does not include characterized genes. The HR-DSCR is annotated as an intergenic region between KCNJ6-201 transcript encoding for potassium inwardly rectifying channel subfamily J member 6 and DSCR4-201 transcript encoding Down syndrome critical region 4. Two transcripts recently identified by massive RNA-sequencing (RNA-Seq) and automatically annotated on Ensembl database reveal that the HR-DSCR seems to be partially crossed by KCNJ6-202 and DSCR4-202 isoforms. KCNJ6-202 shares the coding sequence with KCNJ6-201 which is involved in many physiological processes, including heart rate in cardiac cells and circuit activity in neuronal cells. DSCR4-202 transcript has the first two exons in common with DSCR4-201, the only experimentally verified gene uniquely present in Hominidae. In this study, we performed in silico and in vitro analyses of the HR-DSCR. Bioinformatic data, obtained using Sequence Read Archive (SRA) and SRA-BLAST software, were confirmed by Reverse Transcription-Polymerase Chain Reaction (RT-PCR) and Sanger sequencing on a panel of human tissues. Our data demonstrate that the HR-DSCR cannot be defined as an intergenic region. Further studies are needed to investigate the functional role of the new transcripts, likely involved in DS phenotypes.